2024
DOI: 10.1002/glia.24497
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell‐derived exosomes promote lung cancer progression via miRNA‐21‐5p

Yan Zhou,
Yao Zhang,
Jianlin Xu
et al.

Abstract: Schwann cells (SCs), the primary glial cells of the peripheral nervous system, which have been identified in many solid tumors, play an important role in cancer development and progression by shaping the tumor immunoenvironment and supporting the development of metastases. Using different cellular, molecular, and genetic approaches with integrated bioinformatics analysis and functional assays, we revealed the role of human SC‐derived exosomal miRNAs in lung cancer progression in vitro and in vivo. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Finally, evidence suggests that SCs can play an active role in neoplastic cell invasion and the modulation of immune responses [23,29]. The most often identified mechanism in which this occurs is through the SC activation of M2 macrophages.…”
Section: Schwann Cells and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, evidence suggests that SCs can play an active role in neoplastic cell invasion and the modulation of immune responses [23,29]. The most often identified mechanism in which this occurs is through the SC activation of M2 macrophages.…”
Section: Schwann Cells and Metastasismentioning
confidence: 99%
“…The secretion of paracrine signals or EVs can also accelerate the progression of certain lung cancers, such as lung adenocarcinoma and lung squamous cell carcinoma [29,35]. Paracrine signaling with glial cell line-derived neurotrophic factor (GDNF) from SCs, for example, can increase the invasion of tumor cells along the nerves of the lungs, which are highly innervated [11,37].…”
Section: Lung Cancermentioning
confidence: 99%
“…The results of a new study, using the in vitro and xenogeneic in vivo models of NSCLC, revealed that the promotion of tumor cell proliferation, survival, motility, and transmigration by human SC-conditioned medium was due to SC-derived exosomes ( Zhou et al, 2024 ). Evaluation of the expression and functional activity of SC exosomal microRNA demonstrated that hsa-miRNA-21-5P is responsible for upregulation of NSCLC cell longevity and motility.…”
Section: Introductionmentioning
confidence: 99%
“…These in vitro results were further confirmed by assessing the function of tumor cells transduced with miRNA-21-5p mimic and inhibitor. Additional analysis of tumor cells for intracellular signaling affected by miRNA-21 revealed that reversion-inducing cysteine-rich protein with Kazal motifs (RECK), a matrix metalloproteinase (MMP) inhibitor, not only blocked the interaction with exosomal miR-21-5p but completely prevented activation of tumor cells when transfected into RECK knockout tumor cells in a mutant form ( Zhou et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation